PENGARUH TERPAAN KONTEN TOYOTA LIMO BEKAS TAKSI DI YOUTUBE TERHADAP SIKAP POSITIFPENONTON : Survei Pada Subscribers Youtube Channel Mas Wahid - Lingga Novianto (2021)
The development of technology and information is growing rapidly. The presence of new media such as social media Youtube has made it easier for audiences to find and disseminate information. According to HootSuite and We Are Social's "Global Digital Reports 2021" research, that Youtube social media users are 93.8% of the total Indonesian internet users. Based on the number of Youtube social media users, followed by the number of users who exchange information. Starting from the emergence of a phenomenon on Youtube about the content of used Toyota Limo taxis which had become viral in several circles of society during 2020. Seeing these problems, the researchers then conducted this study with the aim of knowing the magnitude of the influence of exposure to Toyota Limo content ex-taxi on Youtube toward the positive attitude of the audience. In this study, the researcher used the concept of new media, media exposure, content, and the concept of attitude. The researcher used Melvin D. Defleur's theory of individual differences to measure the effect of exposure to ex-taxi Toyota Limo content on Youtube toward the audience's positive attitude. Use short quantitative data. The research method used in this study is a survey method. The population of this research is subscribers from Mas Wahid's Youtube Channel account, then with a sample of 100 respondents. The results of this study indicate that the correlation of variable X to variable Y has a strong relationship with a correlation value of 0.718. Based on the results of the calculation of the coefficient of determination, it shows the influence caused by Exposed Taxi Toyota Limo Content on Youtube toward the positive attitude of the audience by 54.4%, while the rest can be influenced by other factors. Then for the results of hypothesis testing, namely H0 is rejected and Ha is accepted, which means that there is an influence of exposure to used Toyota Limo content on Youtube toward the positive attitude of the audience. Then it is hoped that future research can further examine the factors regarding why the cognitive dimension is the most affected.